PENATALAKSANAAN HOLISTIK PASIEN LAKI-LAKI 52 TAHUN DENGAN SKIZOFRENIA PARANOID DI FASILITAS KESEHATAN PRIMER - Taufiqy, Athaya; Angraini, Dian Isti (CV. Jasa Sukses Abadi, 2024)
Schizophrenia is characterized by fundamental and characteristic deviations from thought and perception, as well as by abnormal affect. Based on Riskesdas in 2019, the prevalence of schizophrenia in Indonesia was 6.7% per 1000 households. Proper handling holistically using a family medicine approach is needed to improve the patient's quality of life. Applying the principles of a holistic and comprehensive family doctor approach in detecting internal and external risk factors and solving EBM problems. This study is a descriptive study of case reports. Primary data were obtained through autoanamnesis and alloanamnesis, mental examination, and home visits. Secondary data were obtained from the patient's medical record. Patient Mr. P, 52 years old, has been diagnosed with schizophrenia paranoid, has difficulty sleeping at night accompanied by frequent talking to himself, hearing voices, and seeing shadows that others cannot see. Furthermore, comprehensive management is carried out, namely carrying out interventions using poster media and inviting patients to socialize. In the evaluation, the results were obtained in the form of a better understanding of the disease and changes in behavior that have an impact on the success of therapy. Holistic management with family medicine approach is needed for patients with paranoid schizophrenia disease to identify problems in various aspects to support the success of therapy and improve the patient's quality of life.